Evaluation of testicular blood flow during testicular torsion surgery in children using the indocyanine green-guided near-infrared fluorescence imaging technique - Xiaomeng Liu; Xiaomeng Liu; Yi Xu; Long Li; Long Li; Dongsheng Bai (Frontiers Media S.A., 2023)
ObjectiveThis study investigates the feasibility of the indocyanine green-guided near-infrared fluorescence (ICG-NIRF) imaging technique in evaluating testicular blood flow during testicular torsion (TT) surgery in pediatric cases.MethodsWe retrospectively analyzed the eight pediatric patients with TT who underwent surgery in our hospital between February and July 2023. The intraoperative two-step method of ICG-NIRF imaging and testicular incision was used to evaluate the testicular blood flow, followed by a selection of different surgical methods. The removed testes were pathologically examined after surgery, and all patients were followed up 1 month after surgery to evaluate testicular blood flow using gray-scale ultrasound and color Doppler flow imaging (CDFI).ResultsEight pediatric TT patients aged 1-16 years, with a median age of 11.5 years, were enrolled. Time from the onset ranged from 4 to 72 h (mean 26.13 ± 25.09 h). A total of eight testes were twisted, including four on the left side and four on the right side. The twisting direction of the testes was clockwise in four cases and counterclockwise in four cases. The rotation of torsion was 180°-1,080° (mean 472.5° ± 396°). There was no statistically significant difference in the imaging time between the four patients with testicular blood vessel imaging on both the torsional and normal sides (P > 0.05). The postoperative recovery was uneventful, with no complications during the follow-up period of 1 month. The postoperative histopathological results of three patients who underwent orchiectomy showed extensive hemorrhage, degeneration, and necrosis of the testicular tissue. Among the five patients who underwent orchiopexy, a gray-scale ultrasound and CDFI examinations showed uniform internal echo of the testes and normal blood flow signals in four patients. One patient with no testicular blood vessel imaging on the torsional side showed uneven internal echo of the testis and no blood flow signals.ConclusionICG-NIRF imaging is a feasible method to evaluate testicular blood flow during TT surgery. Testicular blood vessel imaging within 5 minutes after ICG injection might be the basis for testicular retention during TT surgery.